Peran Satgas PPKS STKIP PGRI Sumenep dalam Upaya Pencegahan dan Penanganan Kekerasan Seksual STKIP PGRI Sumenep - Muslim, Bukhari (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to critically examine the handling of sexual violence in the STKIP PGRI Sumenep campus, because in reality the number of sexual violence in Indonesian universities is increasing every year, including at STKIP PGRI Sumenep itself. The campus as an academic space that should be a comfortable and safe place for knowledge transfer has now turned into a terrible space for students. So this makes the Ministry of Education and Culture and Research and Technology intrigued to issue Minister of Education and Culture Regulation No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence (PPKS) in Higher Education to reduce sexual violence. This was also reinforced by the recommendation to form a PPKS Task Force Team at every campus in Indonesia. This study uses a qualitative approach to all parties involved in the Prevention and Handling of Sexual Violence at STKIP PGRI Sumenep through investigations and interviews as well as collecting data from various relevant and reliable literature. So then the data is re-verified to produce valid data.